V.I. Lenin making a speech on Sverdlov Square in Moscow at the parade of the troops leaving for the Polish front. L.D. Trockij and L.B. Kamenev on the stairs. From: R 531/8. Compare: 69/39 A, page 250-251
V.I. Lenin making a speech on Sverdlov Square in Moscow at the parade of the troops leaving for the Polish front. L.D. Trockij and L.B. Kamenev on the stairs. From: R 531/8. Compare: 69/39 A, page 250-251.